THE ROLE OF THE NATIONAL IDEA IN ELIMINATING IDEOLOGICAL THREATS (Scientific journal of the Fergana State University, 2026)
This article scientifically substantiates ideological threats, factors of their overcoming, the relevance of national ideas and values, which are currently becoming more and more dangerous in the context of globalization in spiritual life and ideological processes, issues concerning all strata of society.